Early anatomy ultrasound in women at increased risk of fetal anomalies. (16th May 2013) - Lim, Janice; Whittle, Wendy L.; Lee, Yee‐Man; Ryan, Greg; Van Mieghem, Tim
ABSTRACT: Objective: This study was designed to assess the accuracy of ultrasound anatomy screening before 17 weeks gestation in a population at high risk of fetal anomalies. Methods: Retrospective review of anatomy ultrasound examinations carried out between 12–17 weeks gestation in a high‐risk population. Early sonographic findings were compared with the 18–22 week anatomy ultrasound, karyotype, echocardiogram and postnatal/postmortem results. Results: A complete anatomical survey was achieved in 68 of 101 screened fetuses (67%), with cardiac anatomy having the lowest completion rate (78/101; 77%). Anomalies were suspected on ultrasound in 23 fetuses. Four of these did not undergo pathologic examination but had clearly abnormal findings on ultrasound. Eighteen fetuses had a confirmed abnormal outcome. Sensitivity of early anatomy ultrasound was 83.3% ( n  = 15/18) and specificity 94.9% ( n  = 75/79). There were 3 false negative ultrasounds (16.6%: trisomy 21 with short humerus, choanal atresia and ventriculomegaly, and a ventricular septal defect). False positive rate was 4.0% (4 ventricular septal defects). Conclusion: The high rate of visualization of anatomic structures between 12–17 weeks gestation allows for either early detection of fetal anomalies or parental reassurance in many cases. Subtle anomalies of the heart remain difficult to diagnose. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Fetal anatomy assessment between 11–13 weeks gestation can detect 40–50% of congenital anomalies. What does this study add? Ultrasound between 12 +0 and 16 +6  weeks gestation in women at high risk of fetal anomalies detects >70% of fetal anomalies, therefore supporting examination slightly later than the first trimester in a high‐risk population. False positivity rate of early anatomy ultrasound is 4.0%.